Food of the grouper Caprodon longimanus from Alejandro Selkirk Island, Chile (Perciformes: Serranidae) - José Rodrigo Rojas M; Sergio Palma; Germán Pequeño R (Revista de Biología Tropical, 1998)
La dieta y preferencia alimentaria de Caprodon longimanus fue estudiada a partir de 55 especímenes capturados en la Isla Alejando Selkirk, Chile entre Noviembre y Diciembre de 1996. Los ejemplares fueron capturados utilizando línea de profundidad. El intervalo de tallas fue 176-286 mm LE. Este serránido es un depredador pelágico zooplactófago oportunista. El componente alimentario más abundante y frecuente fue Thalia sp. (Tunicata:Salpida), con un total de 1655 individuos y 93.3% de frecuencia de ocurrencia. Se identificaron crustáceos (17 géneros), pterópodos, quetognatos y poliquetos. El 14.3% de los estómagos estaba vacío. Diet and food preference of Caprodon longimanus were studied at Alejandro Selkirk Island, Chile. The fishes (N=55) were collected in November and December 1996 using long line and the sizes ranged from 176-286 mm in SL. This grouper is a pelagic opportunistic zooplanktivorous predator. Thalia sp. (Tunicata:Salpida) was the most frequent and abundant prey accounting for 93.3% occurrence based on 1655 individuals. A total of 17 genera of crustaceans as well as pteropods, chaetognaths and polychaete worms were found in the stomach contents. A total of 14.3% of all stomachs were empty.